Predictors of pediatric Henoch-Schönlein purpura recurrence - Santoso, Dara Ninggar; Kurniati, Nia; Hendarto, Aryono; Chozie, Novie Amelia; Prawira, Yogi; Marsubrin, Putri Maharani Tristanita (Paediatrica Indonesiana, 2025)
Background Henoch-Schönlein purpura (HSP) is the most common systemic vasculitis in children and is usually self-limited with a favorable prognosis. However, recurrence in children is associated with a poorer prognosis, i.e., a higher risk of progressing to chronic kidney disease (CKD) as a long-term complication. In Indonesia, the recurrence rate of HSP and its predictors in children have not been well established . Objective To estimate the incidence of recurrent HSP and determine its predictors in children at Dr. Cipto Mangunkusumo National General Hospital (RSCM). Methods A retrospective cohort review of medical records followed children aged <18 years at RSCM for 6 months after HSP diagnosis based on the the European League Against Rheumatism (EULAR)/ Paediatric Rheumatology European Society (PRESS)/Paediatric Rheumatology International Trials Organization (PRINTO) criteria. Multivariate, Cox logistic regression, and Kaplan-Meier analyses were performed. Results This study included 116 children aged 2–17 years with HSP. Twenty-six (22.4%) of the subjects experienced recurrence, with an incidence of 3.56 per 100,000 person-years. The only statistically significant predictor for recurrence was  the presence of infection after the first episode of HSP (HR 11.301; 95%CI 4.327 to 29.519; P<0.001). The cumulative survival of subjects with infection for recurrence over 6 months  was  51%, with mean 5.3 months survival duration (95%CI 4.76 to 5.99; P< 0.0001). Chronic kidney disease, a long-term complication of HSP, was noted in 22 (19%) participants. Conclusion Recurrence of HSP was  observed in 22.4% of our subjects within 6 months follow up. However, subjects with a history of infection after their first episode of HSP resolution should be notified about the possibility of recurrence. Chronic kidney disease occurred in 22 participants (19%), possibly becoming a long-term complication of HSP.